Revisão sistemática sobre competências em Promoção de Saúde - Donzelli, Flávia Teresa Astun (2010)
Introduction: The identification of skills needed for vocational training in health promotion is important to consolidate and expand the practices of the different actions in this field of knowledge. While recent initiatives in order to standardize and define core competencies in health promotion (Consensus of Galway, 2008), it is still necessary to broaden the discussion, in order to compose a language of international cooperation, which will improve the capacity building of professionals in a more homogeneous way. General Objective: Search the world literature for the concepts of competencies in health promotion Specific Objectives: a) identify the different concepts of health promotion competences used in different regions of the world. Method: To develop the theme was chosen as a way to work the systematic literature review. He conducted a survey of articles published in the Pubmed database using the descriptors of Health Promotion, Professional Competence and skills-based education in the period 2000 to 2010, where were found 669 articles. For the sample selection literature was used determined criteria for inclusion and exclusion. After evaluating the methodological rigor of studies through the application of the "Critical Appraisal Skills Programme, CASP (© Milton Keynes Primary Care Trust, 2002) were included as a sample 14 articles from different countries. Results: The results show that there is an international effort to achieve a global consensus about the core competencies in the fields of training professionals to work in health promotion, as vital strategy to create standards for the practice in health promotion. However, the concepts and terms used vary in some respects, revealing that they are influenced by political and cultural factors of each region. The main concepts of competencies were categorized into eight domains present in most of the articles. According to different authors, the most important domains of competence to be developed in vocational training in health promotion are: management, leadership, communication, planning, advocacy, empowerment, knowledge and ability to form partnerships. Some authors stress the need to maintain an active forum for reaching consensus on professional competences, broaden the curricular offerings in different ways in the health promotion, develop health promotion courses in related disciplines, to enhance the actions of academic exchanges between training institutions, foster the development of international courses on health promotion, increase the theoretical and conceptual production of health promotion and its applications and variables.